(untitled) (Research, Society and Development, 2023)
The aim of this review is to expose the main concepts of breast cancer and mastectomy. And as secondary objectives, to point out the consequences on the quality of life of mastectomized patients. The present study is a narrative review of research on mastectomy and the effects of this therapeutic approach on the lives of cancer patients. Aiming to expose scientific productions and reconstruct concepts and lines of thought, articulating knowledge from several renowned works. A search for articles was performed in the Medical Literature Analysis and Retrievel System Online (MEDLINE), Scientific Electronic Library Online (SciELO) and PubMed databases, with the following Health Sciences Descriptors (DeCS): Oncological Surgery; Partial Mastectomy; Total Mastectomy; Malignant Neoplasm; Oncology Patient. Selecting articles between the periods from 2006 to 2023. It is fully proven by the literature that mastectomy changes the lives of cancer patients undergoing the procedure. Postoperative complications are frequently reported in all studies about the surgery, such as: chronic pain, fibrosis, capsular contracture and, above all, social changes and relationships regarding self-esteem. There is the possibility of performing the procedure and then performing breast reconstruction. Benefiting the lives of patients, such as rescuing female affections, a feeling of femininity and bodily integrity, in addition to reducing the impacts of physical changes. In this way, it is understood the need for more scientific productions related to breast reconstruction soon breast cancer, given the benefits and assistance assistance of these women.